2022
DOI: 10.2147/dmso.s375572
|View full text |Cite
|
Sign up to set email alerts
|

Tang-Ping-San Decoction Remodel Intestinal Flora and Barrier to Ameliorate Type 2 Diabetes Mellitus in Rodent Model

Abstract: Purpose Type 2 diabetes mellitus (T2DM) is a complex genetic disease associated with genetic and environmental factors. Previous studies have shown that changes in the gut microbiota may affect the development of host metabolic diseases and promote the progression of T2DM. Tang-ping-san (TPS) decoction can effectively treat T2DM. However, its specific mechanisms must be evaluated. Patients and Methods In the present study, we established an animal model of T2DM using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…The present study showed that the abundances of anti‐inflammatory bacteria, such as Lachnospiraceae_NK4A136_group, Alistipes, Oscillibacter, and Muribaculaceae, were significantly decreased in db/db mice, whereas the abundance of proinflammatory bacteria, such as Lachnoclostridium, was increased. These findings were consistent with those of previous studies 43,44 . Intriguingly, PYR not only modulated the overall structure of the gut microbiota but also selectively enhanced the abundance of anti‐inflammatory bacteria, such as Lachnospiraceae_NK4A136_group, Alistipes, Oscillibacter, and Muribaculaceae, and reduced the abundances of proinflammatory and potentially pathogenic bacteria, such as Blautia, Clostridium_innocuum_group, Lachnoclostridium, Ruminococcus_gnavus_group, and Prevotellaceae UCG‐001, in db/db mice.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study showed that the abundances of anti‐inflammatory bacteria, such as Lachnospiraceae_NK4A136_group, Alistipes, Oscillibacter, and Muribaculaceae, were significantly decreased in db/db mice, whereas the abundance of proinflammatory bacteria, such as Lachnoclostridium, was increased. These findings were consistent with those of previous studies 43,44 . Intriguingly, PYR not only modulated the overall structure of the gut microbiota but also selectively enhanced the abundance of anti‐inflammatory bacteria, such as Lachnospiraceae_NK4A136_group, Alistipes, Oscillibacter, and Muribaculaceae, and reduced the abundances of proinflammatory and potentially pathogenic bacteria, such as Blautia, Clostridium_innocuum_group, Lachnoclostridium, Ruminococcus_gnavus_group, and Prevotellaceae UCG‐001, in db/db mice.…”
Section: Discussionsupporting
confidence: 92%
“…45 Diabetes inhibits the vagus nerve and has deleterious effects on the microbiota and the intestinal tract. 44,46,47 A low vagal tone has been described in diabetes patients, thus favoring peripheral inflammation. 48 Our results showed that the intestinal levels of proinflammatory cytokines (TNF-α, IL-6, and IL-1β) were significantly higher in db/db mice than in db/m mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a negative correlation between Blautia and the serum level of Ile was also found. Several studies showed that Dubosiella presented a decreased abundance in T2DM mice and was significantly negatively related to TG, HOMA‐IR, FBG, TC, and LDL‐c (Li et al, 2022; Yin et al, 2022). However, two conflicting reports showed that Dubosiella presented an increased abundance in T2DM mice and was positively correlated with the circulating level of total BCAAs, Val, and Ile (Bao et al, 2022; Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%